Pelatihan Dasar Jaringan dan Subnetting Menggunakan Media Router Mikrotik - Wijaya Putra, Bambang; Syahputra, M. Efaldes; Parjan; Muhammad Farid, Raihan (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2024)
In the current era of digital transformation 4.0, certainly, technology is an important part of modern society. Mikrotik router is a medium that can be used to engineer networks. Some routeros features that can be done are bandwidth test, torch, mac-ping, mrtg, bridge, firewall & nat, tunnel, user management, etc. The science of static routing is the simplest routing arrangement that can be implemented in engineering internet networks both on a local and interlocal operating system. The purpose of this community service is to provide knowledge to the community about computer network technology and provide an understanding of data security in computer networks and is expected to develop knowledge about computer networks for students, assist the community in learning and understanding the material, and add insight or learning resources, provide information related to understanding the network routing system and security in accessing the internet for lecturers and provide consideration for implementing and developing network learning and subnetting at poltekbang palembang for the study program. The method used in this service is the community participatory method. The implementation of training activities invites the general public from among students and high school students in palembang city. The results of this program are positive efforts in providing understanding to the wider community regarding network data security, as well as dividing the network into more specific networks. This training uses mikrotik routeros media in its implementation.